The Dependence of Javanese Culture in Chinese Temple Ceremony - Hartati, Celerina Dewi (Humaniora: Journal of Indonesia Culture and Society, 2023)
The research discussed the dependence on local culture, in this case, on Javanese culture, in the Chinese temple ceremony. A close relationship between Chinese and Javanese culture could be seen in the cultural interactions between the Chinese and Javanese. This cultural interaction was related to the relationship of the Chinese people with the Javanese cultural values and cultural elements, such as in the ceremony. In cultural interaction, Chinese people were immersed in the values and elements of Javanese culture. Cultural reality had shown, in historical reality, that the Chinese in the past had met, fused, and merged into Java. The research method applied the research was a qualitative descriptive method and case study with an ethnographic approach. This research shows cultural borrowing and dependence on Javanese culture. One of the dependencies of Javanese culture in Chinese culture is ceremony or ritual. Taking the case of the god's birthday ceremony, which is held in temples in Central Java, namely Tek Hay Bio (Semarang) and Welahan, it will be shown that Javanese culture influences Chinese culture. Consequently, the borrowing and dependence on Javanese culture in Chinese culture cause the dominance of Javanese culture in Chinese temple ceremonies and make the loss of some elements of Chinese culture itself (displacement).